Thermal and Electrical Conductivity of Amorphous and Graphitized Carbide‐Derived Carbon Monoliths. Issue 6 (29th February 2016) - Kern, Andreas M.; Zierath, Bodo; Haertlé, Joachim; Fey, Tobias; Etzold, Bastian J. M.
Abstract: The influence of graphitization and composition of carbide‐derived carbon (CDC) monoliths on the electrical and thermal conductivity was investigated. Carbon monoliths with varying porosities were synthesized employing biomorphous macroporous TiC and SiC as precursors. Graphitization was carried out in situ during high‐temperature chlorination with and without addition of nickel, iron, and cobalt chloride to the carbide. The graphitized monoliths showed improved properties. The results demonstrate that despite graphitic carbon also glass‐like carbon, stemming from the carbide synthesis, increases the thermal and electrical conductivity significantly. Abstract : To obtain carbide‐derived carbons with high electrical and thermal conductivities, the influence of the precursor carbide and graphitization procedure was investigated. Especially the amount of glassy carbon stemming from the carbide synthesis can be employed to significantly increase both thermal and electrical conductivities in an easy and low‐cost manner.